2021
DOI: 10.1182/bloodadvances.2020003359
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic and genomic heterogeneity in blastic plasmacytoid dendritic cell neoplasms: from ontogeny to oncogenesis

Abstract: Oncogenesis and ontogeny of blastic plasmacytoid dendritic cell neoplasm (BPDCN) remain uncertain, between canonical plasmacytoid dendritic cells (pDCs) and AXL+ SIGLEC6+ DCs (AS-DCs). We compared 12 BPDCN to 164 acute leukemia by Affymetrix HG-U133 Plus 2.0 arrays: BPDCN were closer to B-cell acute lymphoblastic leukemia (ALL), with enrichment in pDC, B-cell signatures, vesicular transport, deubiquitination pathways, and AS-DC signatures, but only in some cases. Importantly, 1 T-cell ALL clustered with BPDCN,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
52
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(54 citation statements)
references
References 67 publications
2
52
0
Order By: Relevance
“…Our results show that genes encoding RNA splicing components are frequently mutated in BPDCN, with a collective frequency of 23%. Renosi et al [ 27 ] performed NGS targeting 68 genes on 13 cases of BPDCN and detected ZRSR2 mutations in 4 (31%) cases and SRSF2 mutations in 2 (15%) cases. Summerer et al [ 28 ] analyzed 1367 mutations in 1210 genes in 21 BPDCN cases and found mutations in SRSF2 in 7 (33%), SF3B1 in 2 (10%), U2AF1 in 2 (10%), and ZRSR2 in 2 (10%) cases.…”
Section: Discussionmentioning
confidence: 99%
“…Our results show that genes encoding RNA splicing components are frequently mutated in BPDCN, with a collective frequency of 23%. Renosi et al [ 27 ] performed NGS targeting 68 genes on 13 cases of BPDCN and detected ZRSR2 mutations in 4 (31%) cases and SRSF2 mutations in 2 (15%) cases. Summerer et al [ 28 ] analyzed 1367 mutations in 1210 genes in 21 BPDCN cases and found mutations in SRSF2 in 7 (33%), SF3B1 in 2 (10%), U2AF1 in 2 (10%), and ZRSR2 in 2 (10%) cases.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Renosi et al documented the monoallelic deletion of NTRK genes in BPDCN. But the epigenetic control reported in the current study (i.e., acetylation of NRTK1 promoter) may overcome these deletions [ 46 ]. The neurotrophic receptors, known to promote tumor cell proliferation, differentiation, and survival, are emerging as promising therapeutic targets.…”
Section: Discussionmentioning
confidence: 98%
“…In this study, we observe increased expression of IFNA response genes in T-cells relative to Tcells in the healthy controls, initially suggesting higher levels of IFNA production by pDC-like tumor cells. However, previous research on BPDCN has shown that pDC-like tumor cells produce lower levels of IFNA relative to pDCs from healthy individuals (44,45). Further, little research has been reported describing the role of TNFA signaling in BPDCN, though studies have shown increased TNFA signaling in the plasma of patients with acute myeloid leukemia (46,47).…”
Section: Discussionmentioning
confidence: 99%